1995
DOI: 10.1002/eqe.4290241008
|View full text |Cite
|
Sign up to set email alerts
|

Response of rigid body assemblies to dynamic excitation

Abstract: SUMMARYShaking table tests were conducted to investigate the response of rectangular wooden blocks and block assemblies of various sizes and slenderness to harmonic and earthquake base excitation. The shaking tests were followed by an analytical and a numerical study of response of single blocks and block assemblies. The analytical study was aimed at establishing criteria for the initiation of rocking and of overturning in response to harmonic base motion and consisted of solving numerically the differential e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 8 publications
1
48
0
3
Order By: Relevance
“…The friction parameters are varied. For high enough friction, the onset of rocking occurs almost independently of the friction, but depends mainly on the aspect ratio l L , corroborating previous results [57]. For small enough friction, however, there exists a minimum aspect ratio l L under which the onset of rocking starts to depend a lot on friction.…”
Section: Onset Of Rocking With Harmonic Base Excitationsupporting
confidence: 80%
“…The friction parameters are varied. For high enough friction, the onset of rocking occurs almost independently of the friction, but depends mainly on the aspect ratio l L , corroborating previous results [57]. For small enough friction, however, there exists a minimum aspect ratio l L under which the onset of rocking starts to depend a lot on friction.…”
Section: Onset Of Rocking With Harmonic Base Excitationsupporting
confidence: 80%
“…The blocks are separated by joint interfaces, along which the blocks can detach or slide without limit on relative displacement or rotation. Because of these features, DEM is particular suitable for analysing the dynamic behaviour of rocking masonry structures; past studies include investigation of the seismic behaviour of single blocks or block assemblages [21,22,25], masonry arches [23,24], masonry facades [25,26], free-standing columns [27,28] and entire historical structures [29,30].…”
Section: Discrete Element Modellingmentioning
confidence: 99%
“…For example, previous studies [1][2][3] showed that the distinct element method seems to be an e cient tool in predicting the response satisfactorily. However, veri每cation and calibration of the main parameters, especially the joint properties, is necessary, before such a numerical method can be used in the restoration process of a classical monument.…”
Section: Introductionmentioning
confidence: 98%